Introduction special issue: Environmental impacts of illicit economies - Daniel Brombacher; Juan Carlos Garzón-Vergara; María Alejandra Vélez (Journal of Illicit Economies and Development (JIED), 2021)
For decades, illicit economies have predominantly been studied and debated as a security problem with social and development consequences. However, the interaction between illicit economies and the environment, in cases such as illicit drug crop cultivation and drugs production, is more recent and a rather unexplored discussion- despite that it is not a new phenomenon. From an environmental standpoint, illicit economies can lead to a broad array of negative impacts, with complex interactions. This Special Issue of the Journal of illicit Economies and Development seeks to enhance the evidence basis and understanding of the environmental impacts of illicit economies beyond traditional crime-focused indicators. The special issue pursues to shed more light on the manifold interlinkages between illicit economies and the environment, contributing to a growing body of research of a rather young branch of research in the field of illicit economies. The special issue gathers a broad array of phenomena, perspectives, and disciplines, combining original research and policy considerations. The Special Issue includes contributions on the environmental impacts of illicit drug crop cultivation, drug trafficking, drug production, illicit trade in bushmeat and wildlife in general, land grabbing and illicit sand mining, covering a broad range of regions and continents.
Keywords: 330; alternative development; drug policies; environment; environmental crimes; green criminology; Illicit economies; organized crime